RANCANG BANGUN ALAT TIPE SPRAY DRYER UNTUK PROSES PENGERINGAN SUSU BUBUK BERBASIS JAGUNG MANIS (Zea mays saccharata) - Putri, Astri Oktaviana; Mentari, Inez Artemisia; Julyantiya, Robby Try; Yuliati, Selastia; Dewi, Erwana (KINETIKA, 2021)
Drying is one of techniques used in food preservation. Spray Dryer is a type of dryer that can change the feed from a fluid state into granules and then convert again into particles which are dried continuously in hot drying media. Spray dryer uses liquid atomization to form droplets, then the droplets formed are dried using dry air with high temperature and pressure. This 31emperat aims to produce high quality corn porridge milk. The drying process is carried out by a batch process where the material is put into a spray dryer and the process is allowed for a certain period of time. The heat transfer process that occurs in this tool is the main variable to determine the efficiency and performance of the tool produced. The drying process of milk powder was carried out at a temperature of 150Â° C and 160Â°C in 75 minutes. Based on the analysis, the calculation of heat transfer rate, drying rate, and thermal efficiency obtained a powdered milk product of 0.8 grams with a convection heat transfer rate of 1.6924 kJ, a conduction heat transfer rate of 1.299 kJ, a drying rate of 31.594 kg / hour. And thermal efficiency of 35%.